Analysis of Urea Levels of Banjarmasin Ministry of Health Polytechnic Students Survivors of Covid 19 - Hasanah, Siti Nur Shalehah; Thuraidah, Anny; Haitami, Haitami (Baiman Bauntung Batuah Center, 2023)
Corona Virus Disease 2019 (Covid-19) is an infection caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Drug therapy for Covid-19 patients currently uses broad-spectrum antivirals such as Remdesivir, Favipiravir, and Oseltamivir, which have side effects of impaired kidney function with a marked increase in serum urea levels. The study aims to analyze the relationship between antiviral administration and serum urea levels of Covid-19 survivors with student respondents from the Health Polytechnic of the Ministry of Health, Banjarmasin, Indonesia. The research method is an analytic survey with a case-control design. Samples were taken using the purposive sampling method and obtained from 10 respondents who were confirmed positive for Covid-19 who consumed antivirals, ten respondents who were confirmed positive for Covid-19 did not consume antivirals, and ten respondents who were not confirmed positive for Covid-19. The Urea test method uses the Rayto Chemray 120 Clinical Analyzer. The results showed that the average urea level of respondents who confirmed positive for Covid-19 who consumed antivirals was 37.35 mg/dl, and respondents who confirmed positive for Covid-19 who did not consume antivirals was 30.70 mg/dl. Respondents who were not confirmed for Covid-19 19 are 30.97 mg/dl. The study's conclusion showed a relationship between the administration of antivirals and serum urea levels of Covid-19 survivors. Suggestions for further research are to use different parameters in assessing the kidney function of Covid 19 survivors, such as creatinine and blood urea nitrogen.